Developing and implementing 'meta-supervision' for mental health nursing staff supervisees: opportunities and challenges. (14th October 2016) - Buus, Niels; Lynch, Lisa; Gonge, Henrik
Abstract: This paper reports from a study of an intervention aimed at strengthening mental health nursing staff supervision. We developed and tested a short-term group-based meta-supervision intervention as a supplement to usual supervision. The intervention drew on action learning principles to activate and inspire supervisees to develop strategies for influencing their own supervision practices. The core 'meta-supervisory' process was organized round participants' reflections on the possible benefits of supervision, their perceived barriers to realizing the benefits, and the articulation of concrete actions to overcome the barriers. In this paper, we introduce previously reported findings from the study and present two novel supplementary analyses of data from the meta-supervision process. First, we analyse a transcript of an audio recording made during the intervention, which illustrates how supervisees generate empowering psychosocial resources through the group processes. Second, we analyse supervisees' paraphrased accounts of barriers to effective supervision and their accounts of personal projects to overcome the barriers. Barriers 'outside' the supervision setting primarily inspired projects aimed at creating structural change, whereas barriers 'inside' the supervision setting inspired projects aimed at creating individual change. The meta-supervision intervention was effective in increasing participation in supervision, but it shared the same problems of resistance and reluctance as often observed in supervision in general. In the discussion, we compare our 'bottom-up' approach to activating supervisees and implementing supervision practices with 'top-down' approaches. The meta-supervision intervention illustrated the importance of engaging supervisees in their own supervision and suggested how it can have both individual and organizational benefits.